Efeito da hesperidina sobre o déficit cognitivo e o sistema colinérgico de ratos submetidos a um modelo de demência esporádica do tipo Alzheimer - Magni, Luana Pereira (2017)
Alzheimer's disease (AD) is considered the main cause of dementia in the world and the search for new therapeutic interventions for its treatment is of great relevance. Preclinical studies suggest the use of hesperidin (HES), a flavonoid of the subclass flavonone with antioxidant, anti-inflammatory and neuroprotective actions. Thus, the objective of this study was to investigate the effects of treatment with HES and also its effect as an adjuvant in the treatment with rivastigmine on learning and memory parameters and activities of the enzymes acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) in a model sporadic dementia of streptozotocin-induced Alzheimer's disease (STZ) in rats. Sixty male Wistar rats were divided into eight groups (n = 8): control (CTR), rivastigmine 2 mg/kg (RIV), hesperidin 100 mg / kg (HES), rivastigmine + hesperidin (RIV + HES), streptozotocin , streptozotocin + rivastigmine (STZ + RIV), streptozotocin + hesperidin (STZ + HES), streptozotocin + rivastigmine + hesperidin (STZ + RIV + HES). The rats received an injection of STZ (3mg / kg) intracerebroventicular (ICV) and were treated with HES or saline orally for 30 days. The control animals received ICV-saline and were treated with the same solutions. The behavioral investigations were performed 21 days (open field, object recognition) and 30 days (object recognition and passive avoidance task) after the STZ injection. The enzymatic activities of AChE were performed in synaptosomes of the cerebral cortex and hippocampus, as well as in whole blood, and the activity of BuChE in the homogenate of the cerebral cortex and hippocampus. The results revealed that HES, and more significantly HES in association with RIV, was able to attenuate memory loss and increase in the activities of the enzymes of the cholinergic system, demonstrating a neuroprotective effect on animals submitted to this model of dementia. Therefore, it is suggested that this compound may be a potential candidate adjuvant to conventional treatment with RIV in the improvement of the memory deficit caused in AD.